Resolving the identity and breeding habitats of cryptic dipteran cacao flower visitors in a neotropical cacao agroforestry system - Mathil Vandromme; Eliza Van de Sande; Tom Pinceel; Wouter Vanhove; Hendrik Trekels; Bram Vanschoenwinkel (Basic and Applied Ecology, 2023)
Determining the main pollinators and the factors that control their abundance is a prerequisite for improving the production of many crops, including the globally important cash crop cacao (Theobroma cacao L.). Yet, the identity and the breeding habitats of cacao pollinators remain controversial since they are very difficult to identify morphologically due to their small size. It is known that tiny midges are involved in cacao pollination, but their diversity and ecology remain obscure. Here, we combined the collection of flower visitors, the use of emergence traps, and DNA barcoding to assess the diversity of dipteran cacao flower visitors and link them to five candidate breeding habitats in an agroforestry system in central Nicaragua. We detected 59 lineages of dipteran flower visitors, including Cecidomyiidae, Ceratopogonidae, Chironomidae, and Sciaridae, suggesting that dipteran cacao pollinator diversity may be much higher than previously assumed. Five lineages could be genetically traced back to specific breeding habitats. We conclude that the presented approach can be a promising tool to reliably delineate potential pollinator species and their breeding habitats, which can inform management strategies to promote cacao pollination.